Validation of Vanillylmandelic Acid (VMA) with Plasma Metanephrine and Normetanephrine for Screening Adrenal Medullary Disorders - Usama Bin Khalid; Zujaja Hina Haroon; Muhammad Aamir; Sana Ashraf; Afshan Bibi; Haroon Javaid (Pakistan Armed Forces Medical Journal, 2023)
Objective: To validate urinary Vanillylmandelic acid (VMA) for screening adrenal medullary disorders, taking plasma-free Metanephrine as the gold standard.